Diagnostic tests and subtypes of dysfunctional breathing in children with unexplained exertional dyspnea. Issue 10 (11th July 2022) - Peiffer, Claudine; Pautrat, Jade; Benzouid, Chérine; Fuchs‐Climent, Deborah; Buridans‐Travier, Nellie; Houdouin, Véronique; Bokov, Plamen; Delclaux, Christophe
Abstract: Background: Inappropriate hyperventilation during exercise may be a specific subtype of dysfunctional breathing (DB). Objective: To assess whether Nijmegen questionnaire and hyperventilation provocation test (HVPT) are able to differentiate inappropriate hyperventilation from other DB subtypes in children with unexplained exertional dyspnea, and normal spirometry and echocardiography. Methods: The results were compared between a subgroup of 25 children with inappropriate hyperventilation (increased V'E/V'CO2 slope during a cardiopulmonary exercise test (CPET)) and an age and sex matched subgroup of 25 children with DB without hyperventilation (median age, 13.5 years; 36 girls). Anxiety was evaluated using State‐Trait Anxiety Inventory for Children questionnaire. Results: All children were normocapnic (at rest and peak exercise) and the children with hyperventilation had lower tidal volume/vital capacity on peak exercise (shallow breathing). The Nijmegen score correlated positively with dyspnea during the CPET and the HVPT ( p  = 0.001 and 0.010, respectively) and with anxiety score ( p  = 0.022). The proportion of children with a positive Nijmegen score (≥19) did not differ between hyperventilation (13/25) and no hyperventilation (14/25) groups ( p  = 0.777). Fractional end‐tidal CO2 (FETCO2 ) at 5‐min recovery of the HVPT was < 90% baseline in all children (25/25) of both subgroups. Likewise, there was no significant difference between the two subgroups for other indices of HVPT (FETCO2 at 3‐min recovery and symptoms during the test). Conclusion: The validity of the Nijmegen questionnaire and the HVPT to discriminate specific subtypes of dysfunctional breathing, as well as the relevance of the inappropriate hyperventilation subtype itself may both be questioned.